An Improved Computationally Efficient Method for Finding the Drazin Inverse - Haifa Bin Jebreen; Yurilev Chalco-Cano (Discrete Dynamics in Nature and Society)
Drazin inverse is one of the most significant inverses in the matrix theory, where its computation is an intensive and useful task. The objective of this work is to propose a computationally effective iterative scheme for finding the Drazin inverse. The convergence is investigated analytically by applying a suitable initial matrix. The theoretical discussions are upheld by several experiments showing the stability and convergence of the proposed method.